Analisis Putusan Hakim Pada Perkara Tindak Pidana Mineral Dan Batubara: Studi Putusan Pemidanaan Pada Masyarakat Adat Maba Sangaji Di PN Soasio - Amin Yasim; Faissal Malik; Nam Rumkel (Supremasi Hukum: Jurnal Penelitian Hukum, 2026)
This study aims to analyze the judges' legal considerations in deciding a mineral and coal mining (Minerba) crime case involving the Maba Sangaji indigenous community at the Soasio District Court. The main problem in this study is how the judges' legal considerations in deciding the mineral and coal crime case in the verdict (A Study of Criminal Decisions for the Maba Sangaji Indigenous Community at the Soasio District Court). The research method used is normative legal research with a statutory approach, a case approach, and a conceptual approach. The data used consists of primary, secondary, and tertiary legal materials analyzed qualitatively. The results of the study indicate that the judge's considerations in the Mineral and Coal Mining crime case involving the Maba Sangaji indigenous community focused more on fulfilling the elements of the crime as stipulated in Law Number 3 of 2020 concerning Mineral and Coal Mining, as amended by Law Number 4 of 2009. In the judge's decision, with the indictment of Article 162 of the Mineral and Coal Mining Law, without optimally considering the existence and traditional rights of indigenous legal communities guaranteed by Article 18 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, the decision has legal implications in the form of weak legal protection for indigenous communities in managing their territories, and has the potential to criminalize traditional community activities that have been carried out for generations. This research is expected to contribute to academics in the development of law enforcement officials and policy makers to pay more attention to the principles of substantive justice and recognition of the rights of indigenous communities in law enforcement.